2015
DOI: 10.1096/fj.14-268482
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent impairment of glucose tolerance in the 3xTg‐AD mouse model of Alzheimer's disease

Abstract: Alzheimer's disease (AD) has been associated with type II diabetes (T2D) and obesity in several epidemiologic studies. To determine whether AD neuropathology can cause peripheral metabolic impairments, we investigated metabolic parameters in the triple-transgenic (3xTg)-AD mouse model of AD, compared with those in nontransgenic (non-Tg) controls, at 6, 8, and 14 mo of age. We found a more pronounced cortical Aβ accumulation (2- and 3.5-fold increase in Aβ42 in the soluble and insoluble protein fractions, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
93
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 82 publications
(121 reference statements)
15
93
0
1
Order By: Relevance
“…1C). Taken together, these data suggest peripheral glucose insulin resistance in 16-month-old 3xTg-AD mice; this finding is consistent with previous reports (Vandal et al, 2015). …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…1C). Taken together, these data suggest peripheral glucose insulin resistance in 16-month-old 3xTg-AD mice; this finding is consistent with previous reports (Vandal et al, 2015). …”
Section: Resultssupporting
confidence: 93%
“…Specifically, phosphorylated IRS recruits the heterodimeric p85/p110 PI3K at the plasma membrane, where it produces the second messenger phosphatidylinositol-4,5-bisphosphate 3- (PIP3) kinase, which in turn activates a serine/threonine phosphorylation cascade of PH-domain containing proteins (Alessi and Downes, 1998). PIP3 targets include PDK1, the serine/threonine protein kinase B (PKB)/Akt, and the atypical protein kinases C ζ and λ isoforms (Dineley et al, 2014; Vandal et al, 2015). GSK-3β, a convergent target of the PDK1/AKT pathways, induces glycogen synthesis through the target of rapamycin complexes to control AMP-activated protein kinase (AMPK), energy metabolism, mitochondrial function, synaptic plasticity and memory (Cheng et al, 2010; Kleinridders et al, 2014; Stoica et al, 2011; White, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicates that the prion promoter itself may be a useful tool for driving robust gene expression of target genes specifically within the endocrine compartment of the pancreas. It has recently been reported that a 3xTg-AD model of Alzheimer’s disease, which uses Thy 1.2 promoter, also overexpresses human APP within pancreatic islets (Vandal et al 2015). Because of the similarity in gene expression and phenotype between pancreatic islets and neurons, it is likely that numerous genetic elements which drive high expression of genes in the central nervous system will also result in robust islet gene expression (Atouf, et al 1997; Martens, et al 2011; Moller, et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports of the detection of amyloid beta within human islets (Miklossy, et al 2010; Oskarsson, et al 2015). Increased levels of Aβ or Aβ aggregates have been detected within the pancreas of some transgenic mouse models of AD (Shoji, et al 1998; Shoji, et al 2000; Vandal, et al 2015; Wegiel, et al 2000). …”
Section: Introductionmentioning
confidence: 99%